Stream zoobenthos under extreme conditions in the high Andean plateau of Argentina (South America) - Rodrigues Capitulo, Alberto (2014)
The Puna de Atacama plateau (South America; altitude 3800 m)dwith its endorheic basins and containing one of the principal deposits of lithium worldwidedis one of the most extensive tablelands on the planet. Information on the invertebrates of those internal catchment areas, however, is scarce and fragmentary. We describe here for the first time the structure and composition of the invertebrate assemblage of the Olaroz Salar (Argentina), analyze the spatial-temporal changes, and examine the relationships between the organisms and their environment. Samplings of the sediment and aquatic vegetation were carried out in three affluent streams of the salar during the wet season and the limnologic variables were measured in situ. Of the 26 taxa collected, the most highly represented were Nematoda, Harpacticoida, Paranais litoralis, and Limnocythere sp.; while Heterocypris incongruens registered the highest abundance. The total density was correlated with the sediment organic matter and differed among the streams. The abundance, richness, and diversity decreased upon proximity to the salar. The invertebrate assemblage varied spatially, with the conductivity gradient being one of the principal conditions influencing the distribution. Redundancy-detrended analysis demonstrated that within these environments the conductivity, amount of organic matter, and vegetation were the principal determinants of benthic development. The insularity, fragility, and low resilience of these wetlands necessitate adequate administration policies for their long-term management and utilization, particularly in view of the growing demand for mineral exploitation in the region.